Design and Development of RFID based Software Framework Prototype for Smart Home - Deka, Vaskar; Kumar Sharma, Shikhar (International Journal of Computer Sciences and Engineering, 2025)
The concept of home automation for realizing the remote access cum control of electrical appliances has been migrating to the concept of smart environment by the rapid incorporation of the information and communications technologies. In this regard, several research works are currently going on all around the globe by different researchers of different technical fields at different levels. This work is to design an efficient software framework for smart home environment through the use of RFID communication technology for identifying the presence of inhabitants individually and also for providing the required services accordingly from the environment based on previous behaviors of the individuals. One algorithm/ method has been introduced in this work to identify the user on his/ her presence in the environment and also to access the required information from the system database about the services, as per his/ her previous settings of the appliances. Again another one data mining based algorithm is also introduced in this work in order to learn the association of the appliances available in the environment so that proactive services from the environment can be initiated. The work is mainly to focus over the sensing and processing part of the proposed smart home environment, rather than giving stress over the deployment of real actuators and hence the status of the appliances has been shown in GUI based platform. This work concludes with challenges related to the smart home environment in order to make the entire technology more efficient and robust.